2003
DOI: 10.1097/00004032-200305000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Inter-Species Extrapolation of Skin Heating Resulting From Millimeter Wave Irradiation: Modeling and Experimental Results

Abstract: This study reports measurements of the skin surface temperature elevations during localized irradiation (94 GHz) of three species: rat (irradiated on lower abdomen), rhesus monkey (posterior forelimb), and human (posterior forearm). Two exposure conditions were examined: prolonged, low power density microwaves (LPM) and short-term, high power density microwaves (HPM). Temperature histories were compared with calculations from a bio-heat transfer model. The mean peak surface temperature increase was approximate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The temperature results of figure 2 are consistent with and qualitatively similar to published skin heating curves obtained during low-power, far-field CW exposure at 94 GHz in three different species (rat, monkey, human) (Nelson et al 2003).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The temperature results of figure 2 are consistent with and qualitatively similar to published skin heating curves obtained during low-power, far-field CW exposure at 94 GHz in three different species (rat, monkey, human) (Nelson et al 2003).…”
Section: Discussionsupporting
confidence: 87%
“…One method proposed for measurement of blood flow in the skin microvasculature is monitoring temperature response to low-power, radio frequency radiation in the millimeter wave (MMW) band (30-300 GHz) (Nelson et al 2003, Walters et al 2004. The ability to relate the temperature increase to tissue perfusion during MMW exposure could yield a simple, non-invasive method for measuring the rate of blood flow to the dermis.…”
Section: A Nelson Et Almentioning
confidence: 99%
“…Therefore, the skin is the likely location of the initial response to millimeter waves and is a primary target of interest for investigating potential biological effects (1). Some of the emerging technologies mentioned previously involve sources with operating frequencies that include 35 GHz (8) and use power levels at or above those that have been shown to cause significant temperature elevations at the skin surface and subcutis for 35 GHz and higher frequencies (9)(10)(11). Reviews of known hazards of radiofrequency radiation indicate that the health effects of greatest concern are expected to result from overexposures involving temperature increases in tissues (2).…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously reported that during longer exposures skin blood flow increased due to heating of cutaneous vasculature [Nelson et al 2003;Walters et al 2004]. Heat, then, would be most concentrated at or near the penetration depth of 94 GHz.…”
Section: Discussionmentioning
confidence: 94%